Why Do Physiotherapists Do What They Do? A Study of Kuwaiti Physiotherapists. (18th August 2015) - Al‐Enezi, Latifa; May, Stephen
Abstract: Background and Purpose: Physiotherapy has an important role in the management of numerous musculoskeletal (MSK) problems. In terms of evidence‐based physiotherapy practice, little is known about the reasons for selection of treatment techniques by MSK physiotherapists or whether their treatments are evidence based. This survey aimed to explore the reasons for the choice of treatment techniques by Kuwaiti MSK physiotherapists and to identify the extent of using the evidence base from research findings as a basis for physiotherapy practice. Methods: A self‐reported questionnaire accompanied with participant information sheet was distributed to 139 MSK physiotherapists in seven hospitals in Kuwait. The questionnaire was modified from that used in a previous study for use with Kuwaiti MSK physiotherapists to include modalities that were known to be used there by the lead author. It was piloted prior to distribution on three Kuwaiti MSc students for content and face validity. Results: One hundred six of 139 therapists responded, of whom 22% were male and 78% were female. The study showed that undergraduate education was the main influence for all treatment techniques used by Kuwaiti MSK physiotherapists. The use of research findings as a basis for choice of treatment techniques was very limited. The use of research was not related to post‐qualification education or years of professional experience. Conclusion: The findings of this study demonstrate that current physiotherapy practice in Kuwait is more reliant on undergraduate education and less on research evidence for the choice of treatment techniques. This has implications for undergraduate physiotherapy curricula, suggesting that evidence‐based practice must be keenly espoused. Copyright © 2015 John Wiley & Sons, Ltd.